2011
DOI: 10.1007/s00595-010-4349-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic one-stage resection of right and left colon complicated diverticulitis equivalent to hinchey stage I–II

Abstract: Our findings indicate that laparoscopic surgery can be performed safely and effectively even for patients with Hinchey I-II, I'-II' colonic diverticulitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Accordingly, recurrent colonic diverticulitis without abscess or perforation alone is not an indication for surgery (and is not an indication for preventive colectomy). Elective surgery is considered based on the state of immunodeficiency (e.g., post-transplantation), severity of recurrent diverticulitis, presence of comorbidities, and age [156][157][158].…”
Section: Cq33: Is Antibiotic Therapy Recommended For Colonic Diverticmentioning
confidence: 99%
“…Accordingly, recurrent colonic diverticulitis without abscess or perforation alone is not an indication for surgery (and is not an indication for preventive colectomy). Elective surgery is considered based on the state of immunodeficiency (e.g., post-transplantation), severity of recurrent diverticulitis, presence of comorbidities, and age [156][157][158].…”
Section: Cq33: Is Antibiotic Therapy Recommended For Colonic Diverticmentioning
confidence: 99%
“…According to Lin et al, 15.2% patients developed wound infections one patient developed intra-abdominal bleeding [37]. In Katsuno et al, wound infection was found in 6.4% of patients in the LA [38]. In Ansari et al, out of 103 patients who were successfully operated laparoscopically, 21 patients developed minor complications like fever in 11 (10.67%) patients, 5 (4.85%) patients had post-operative ileus that postponed their begin of oral ingestion and 5 (4.85%) patients had port site infection [33].…”
Section: Discussionmentioning
confidence: 97%
“…Piskun et al, data on 52 patients with perforated appendicitis 10 (19%) had converted appendectomies. 10 13 In Ansari et al, out of 103 patients who were successfully operated laparoscopically, 21 patients developed minor complications like fever in 11 (10.67%) patients, 5 (4.85%) patients had postoperative ileus that delayed their start of oral intake and 5 (4.85%) patients had port site infection. There were no cases of postoperative bowel obstruction and no mortality.…”
Section: Discussionmentioning
confidence: 99%